RESULTADOS DO PROJETO DE PESQUISA EM MECATRÔNICA NA UNIJUÍ OBTIDOS EM 2007 - Valdiero, Antonio C.; Andrighetto, Pedro L.; Rafikov, Marat; Dilda, Vanessa; Dilda, Vanessa; Miotto, Fabiane E. M.; Ritter, Carla S.; Locateli, Cristiano C.; Schmitt1, Paulo R.; Zago, Fernando (Salão do Conhecimento, 2013)
Resumo